1998
DOI: 10.3109/13651509809115108
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and the elderly

Abstract: Impending demographic changes mean that the proportion of the elderly in the population will increase. Suicide rates increase with age. The literature on elderly suicide, with emphasis on methodology, cross-national rates and trends, correlates, cultural factors, location and method, attempted suicides and prevention, is critically reviewed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
164
3
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 163 publications
(188 citation statements)
references
References 153 publications
18
164
3
3
Order By: Relevance
“…The finding that rates for violent methods of suicide were higher in older males than females, have also been previously observed (Shah and De, 1998;Harwood et al, 2000;Hoxey and Shah, 2000;Tadros and Salib, 2000;Salib and Green, 2003). However, this study also found that older men had higher rates of drowning than older women, which although supporting the findings of Hoxey and Shah (2000), was contrary to the results of Harwood et al (2000), who found that this method was more common in older women than men.…”
Section: Comparison Of Rates Of Suicide Methods Used By the Elderly Icontrasting
confidence: 57%
See 2 more Smart Citations
“…The finding that rates for violent methods of suicide were higher in older males than females, have also been previously observed (Shah and De, 1998;Harwood et al, 2000;Hoxey and Shah, 2000;Tadros and Salib, 2000;Salib and Green, 2003). However, this study also found that older men had higher rates of drowning than older women, which although supporting the findings of Hoxey and Shah (2000), was contrary to the results of Harwood et al (2000), who found that this method was more common in older women than men.…”
Section: Comparison Of Rates Of Suicide Methods Used By the Elderly Icontrasting
confidence: 57%
“…Although rates for poisoning by antiepileptic, sedative-hypnotic, anitparkinsonism and psychotropic drugs were higher in older women than men, these result were non significant. In addition, for all other forms of suicide by poisoning the rates were higher for older men than women, but again these were non significant.The finding that overall rates were significantly higher in older than younger men was as expected, as traditionally suicide rates increase with ageing (Shah and De, 1998). A similar trend was found for females, although these did not reach statistical significance.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Risk factors attributable to age, period, and cohort membership can independently influence suicide rates at a given age and given time in a given birth cohort (Shah and De, 1998). Suicide rates in individuals born in a particular cohort are peculiar to that cohort -the cohort effect.…”
mentioning
confidence: 99%
“…Proximal risk and protective factors have generally been examined either descriptively in case-series of elderly suicide victims (Shah and De, 1998) or analytically in case-control studies (Waern et al, 2003). Such studies have primarily examined linear relationships between suicide and proximal risk and protective factors.…”
mentioning
confidence: 99%